A call for strategic water-quality monitoring to advance assessment and prediction of wildfire impacts on water supplies - Murphy, Sheila F.; Alpers, Charles N.; Anderson, Chauncey W.; Banta, J. Ryan; Blake, Johanna M.; Carpenter, Kurt D.; Clark, Gregory D.; Clow, David W.; Hempel, Laura A.; Martin, Deborah A.; Meador, Michael R.; Mendez, Gregory O.; et al. (Frontiers in Water, 2023)
Wildfires pose a risk to water supplies in the western U.S. and many other parts of the world, due to the potential for degradation of water quality. However, a lack of adequate data hinders prediction and assessment of post-wildfire impacts and recovery. The dearth of such data is related to lack of funding for monitoring extreme events and the challenge of measuring the outsized hydrologic and erosive response after wildfire. Assessment and prediction of post-wildfire surface water quality would be strengthened by the strategic monitoring of key parameters, and the selection of sampling locations based on the following criteria: 1) streamgage with pre-wildfire data; 2) ability to install equipment that can measure water quality at high temporal resolution, with a focus on storm sampling; 3) minimum of 10% drainage area burned at moderate to high severity; 4) lack of major water management; 5) high-frequency precipitation; and 6) availability of pre-wildfire water-quality data and (or) water-quality data from a comparable unburned basin. Water-quality data focused on parameters that are critical to human and (or) ecosystem health, relevant to water-treatment processes and drinking-water quality, and (or) inform the role of precipitation and discharge on flow paths and water quality are most useful. We discuss strategic post-wildfire water-quality monitoring and identify priority areas for longer-term post-wildfire water-quality monitoring and assessment. Improved estimates of the magnitude, timing, and duration of post-wildfire effects on water quality would aid the water resources community prepare for and mitigate against impacts to water supplies.